Last Barriers : Photographs of Wilderness in the Gulf Islands National Seashore - Bradburn, Donald Muir (Book collections on Project MUSE., 2011)
Rarely has a book of photography performed a more poignant and immediate service in preserving a natural Mississippi wonder. The Mississippi Gulf Coast barrier islands captured the heart and mind of Donald Bradburn (b. 1924) in childhood. He became fascinated with the natural history and ornithology he witnessed. To him, the islands, especially Horn Island with its dark forests, high dunes, and deserted beaches, represented unbounded freedom and the ideal of a timeless world. Years later, when the National Park Service threatened to open the islands to "almost unlimited opportunities for.